Moderation of Islamic Education in Higher Education - Fuad, A. Jauhar; Mila, Asep Saiful (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2022)
This paper explores the moderation of Islamic Religious Education in higher education. This paper is the result of library research by collecting several research journals related to the theme of writing. Higher education as an educational institution that creates the nation's next generation plays an important role in growing the concept of religious moderation. Higher education is a representation in instilling a tolerant attitude of students towards differences in beliefs in Indonesia. Reflecting on the issue of sara that disturbs the sensitivity of certain communities, it opens up conflicts that continue to occur now and in the future. The conflict must be closed immediately in order to prevent divisions in the life of the nation and state. Disputes, strife, and bloodshed. Moderate Islam can solve all problems related to intolerance and understanding that can disrupt the stability of the country such as radicalism, extremism, as well as other forms of discrimination. In this context, to strengthen the ideology and character of the nation's generation, universities must effectively instill and strengthen an understanding of religious moderation. For example, carrying out the function of moderating religious houses, providing moderate Islamic learning and realizing inter-religious harmony.